Solve differential equation y'+3y= 3x^2 e^(-3x)

OlmekinjP 2021-02-09 Answered
Solve differential equationy+3y=3x2e(3x)
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

hajavaF
Answered 2021-02-10 Author has 90 answers

y+3y=3x2e3x
Compairing with genral form of a linear diffrential equation
y+Py=θ
with integrating factor IF=ePdx
we have P = 3, θ=3x2e3x
I.F.=e3dx=e3x
:. Its solution is given by
y(I.F.)=θ(I.F.)dx+C
ye3x=3x2e3x3xedx+C
ye3x=3x2dx+C
ye3x=(3x3)/3+C
ye3x=x3+C
y=e3x(x3+C)

Not exactly what you’re looking for?
Ask My Question
Jeffrey Jordon
Answered 2021-12-14 Author has 2070 answers

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Relevant Questions

asked 2022-01-22
Solve the first-order differential equations:
(x2+1)dydx=xy
asked 2021-02-20
Solve differential equation dy/dx=(y21)/(x21)
asked 2021-02-12
Solve the differential equation (dP)/dt=4P+a
asked 2022-05-28
I would need some help in solving the following differential equation:
u ( p ) + r + N λ p N λ p ( 1 p ) u ( p ) = r + N λ p N λ ( 1 p ) g .
I already know that the solution is of the form
g p + C ( 1 p ) ( 1 p p ) r / λ N ,,
where C is a constant.
Now this is a standard linear first-order differential equation. Letting
f ( p ) = r + N λ p N λ p ( 1 p ) ,     q ( p ) = r + N λ p N λ ( 1 p ) g ,     μ ( p ) = e f ( p ) d p ,
the solution should have the form
u ( p ) = C μ ( p ) + 1 μ ( p ) μ ( p ) q ( p ) d p ,
where C is a constant.
The calculation of μ ( p ) was not much of a problem. Indeed, we can rewrite f(p) as
f ( p ) = r N λ 1 p + ( 1 + r N λ ) 1 1 p
Using 1 p d p = ln ( p ) and 1 1 p d p = ln ( 1 p ), I found that
μ ( p ) = p r N λ ( 1 p ) 1 r N λ .
Where I have difficulties is calculating the term ∫μ(p)q(p)dp, where
μ ( p ) q ( p ) = r g N λ p r N λ ( 1 p ) 2 r N λ + p r N λ + 1 ( 1 p ) 2 r N λ .
How do I integrate this last term? Or did I miss something obvious, because in the paper I'm looking at they don't provide any details about how they get to the solution of the differential equation
Edit: small typo corrected in the last displayed equation.
Edit: there is a big typo in the differential equation: the rhs should have r + N λ rather than r + N λ p in the numerator. This probably makes it much simpler to solve. My bad.
asked 2020-11-08
Solve differential equationxy=(1y2)12
asked 2022-05-13
I am curious if there are any examples of functions that are solutions to second order differential equations, that also parametrize an algebraic curve.
I am aware that the Weierstrass - Elliptic function satisfies a differential equation. We can then interpret this Differential Equation as an algebraic equation, with solutions found on elliptic curves. However this differential equations is of the first order.
So, are there periodic function(s) F ( x ) that satisfy a second order differential equation, such that we can say these parametrize an algebraic curve?
Could a Bessel function be one such solution?
asked 2020-11-08

Given the function {etif 0t<20if 2t
Express f(t) in terms of the shifted unit step function u(t -a)
F(t) - ?
Now find the Laplace transform F(s) of f(t)
F(s) - ?